Safety and Clinical Effects of Switching From Intravenous to Oral Nimodipine Administration in Aneurysmal Subarachnoid Hemorrhage - Göttsche, Jennifer; Schweingruber, Nils; Groth, Julian Christopher; Gerloff, Christian; Westphal, Manfred; Czorlich, Patrick (Frontiers in Neurology, 2021)
Objective: Several guidelines recommend oral administration of nimodipine as vasospasm prophylaxis after aneurysmal subarachnoid hemorrhage (SAH). However, in clinical practice, the drug is administered orally and intravenously (i.v.), depending on clinical conditions and local treatment regimens. We have therefore investigated the safety and clinical effects of switching from i.v. to oral nimodipine therapy. Methods: Patients with aneurysmal SAH between January 2014 and April 2018 and initial i.v. nimodipine therapy, which was subsequently switched to oral administration, were included in this retrospective study. Transcranial Doppler sonography (TCD) of the vessels of the anterior circulation was performed daily. The occurrence of vasospasm and infarction during the overall course of the treatment was recorded. Statistical level of significance was set to p<0.05. Results: A total of 133 patients (mean age 55.8 years, 65% female) initially received nimodipine i.v. after aneurysmal SAH, which was subsequently switched to oral administration after a mean of 12 days. There were no significant increases in mean flow velocities on TCD after the switch from i.v. to oral nimodipine administration regarding the anterior cerebral artery. For the middle cerebral artery, an increase from 62.36 cm/sec to 71.78 cm/sec could only be detected in the subgroup of patients with infarction. There was no clustering of complicating events such as new-onset vasospasm or infarction during or after the switch. Conclusions: Our results do not point to any safety concerns when switching nimodipine from initial i.v. to oral administration. Switching was neither associated with clinically relevant increases in TCD velocities nor other relevant adverse events.